If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(2x+3)-2(x+5)=20
We move all terms to the left:
4(2x+3)-2(x+5)-(20)=0
We multiply parentheses
8x-2x+12-10-20=0
We add all the numbers together, and all the variables
6x-18=0
We move all terms containing x to the left, all other terms to the right
6x=18
x=18/6
x=3
| 5x-28=7x-44 | | 8n-5(-8n-4)=20+7n | | -3(4v-8)=-36 | | p+52=5p-4 | | 64a×4=44 | | p+52=5p4 | | -9(x8)=63 | | 9(x-6=) | | v+8=4v-19 | | 4x+7=x+(7-2x) | | 3a+19=5a-12 | | 11x+6=3x-2 | | 5/3=6/x-2 | | 75x+6.25=90+4.75 | | 10x=7-70 | | 1.2/x=4 | | 3x=x+92 | | 4y=y+92 | | 3x=x+49 | | 3x-x+2x+12=3x+9 | | 3(y+2)+y=4(y-1+9 | | 10z=7z-41 | | 60+2s=125 | | 6g+20=2g+20 | | 4y=y+39 | | 6g+12=2g+2” | | 7-2x+7x=8 | | -1-6x=4-8x+3x | | 4b+3(2b+6)=7b+24 | | 40+.25m=25+.35m | | 16+11t=71 | | D=1/2t+3 |